Fungsi dan Peran Kepemimpinan Kiai dalam Pengembangan Pondok Pesantren di Pondok Pesantren Sukamiskin dan Miftahul Falah Bandung - Muhammad Abdul Rojak; Iing Solihin; Ahmad Halil Naufal (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
Kyai is a core factor and a central figure in pesantren because all the organizing of pesantren is centered on him. Individual-charismatic leadership in pesantren for certain purposes is needed, but at the same time can also be a weakness of pesantren. Thus, kyai's functions and leadership roles are seen as important to answer the challenges of the times. Pondok Pesantren Sukamiskin and Miftahul Falah are experiencing developments based on the strong leadership role of kiai in pesantren. The purpose of this research is to find out the functions and leadership roles of kyai in sukamiskin boarding school and Miftahul Falah Bandung. This study uses qualitative descriptive methods. The result of this study is known that Pondok Pesantren Sukamiskin and Miftahul Falah have undergone a leadership transformation by applying the tradition of leadership kyai pesantren which aims to develop pesantren. From the existing thing that kyai leadership role has occurred by not eliminating the characteristics of pesantren.